Pengaruh Financial Knowledge, Pendapatan, Locus of Control, Financial Attitude, Financial Self-Efficacy, dan Parental Financial Socialization terhadap Financial Management Behavior Masyarakat di Kabupaten Sidoarjo - Harianto, Sustiko; Isbanah, Yuyun (Jurnal Ilmu Manajemen, 2021)
The Indonesian community's ratio is very high compared to the savings rate. This study aims to analyze the factors that influence the financial management behaviour of the Sidoarjo community. The factors used in this study are financial knowledge, income, locus of control, financial attitude, financial self-efficacy, and parental financial socialization. This study uses quantitative data with the Sidoarjo community as a population. This study's analysis technique is multiple linear regression analyses with 220 samples of respondents. The result shows that income and locus of control can affect financial management behaviour, and financial knowledge, financial attitude, financial self-efficacy, and parental financial socialization does not affect financial management behaviour. The income can affect financial management behaviour because when someone has good money resources, they can pay all of their bills and make some savings and investment.